Business uncertainty, corporate decision and startups. (15th May 2018) - Pomerol, Jean-Charles
Abstract: In this paper, we argue that transformational entrepreneurs generate some uncertainty in business. This uncertainty must not be exaggerated; it is relatively low for incumbent business but is increasing and thus must be considered. One way of dealing with this non-probabilistic uncertainty is to have an adequate decision policy regarding startups, either following them and eventually acquiring them or encouraging innovation inside and facilitating swarming. We examine what can be the consequence: startup bubbling coming at its end or continuing.